EMBR-04. WHAT THE FOX SAY? A MOLECULAR ANALYSIS OF FOXR2 IN PEDIATRIC BRAIN TUMORS. Issue 2 (22nd June 2018) - van Rijn, Sjoerd; Vouri, Mikaella; Pfister, Stefan M; Kawauchi, Daisuke; Kool, Marcel
Abstract: FOXR2 is a transcription factor and has been identified as a putative oncogene in various human cancers but its oncogenic mechanism remains largely unknown. Recently, we identified four new pediatric brain tumor entities among molecularly re-classified CNS-PNETs. The genetic hallmark of one of these new entities, designated as CNS NB-FOXR2, is a genomic aberration present in nearly all cases that leads to transcriptional activation of FOXR2. FOXR2 is not expressed in normal brain and most other brain tumor entities. Only some SHH medulloblastomas and pediatric glioblastomas show FOXR2 expression that we observed to be caused by similar genomic aberrations as in CNS NB-FOXR2 tumors. Interestingly, transcriptome and genomic analyses show that FOXR2 activation in CNS NB-FOXR2, SHH MB, and GBM tumors is mutually exclusive from MYC(N) activation, but expression profiles of FOXR2 activated tumors are still highly similar to MYC(N) activated tumors. These data suggest that FOXR2 may either interact with MYC(N) or activate the same set of genes independent from MYC(N). To investigate the function of FOXR2 in these brain tumors and how it may interact with MYC(N), we overexpressed FOXR2 w/o MYC(N) in human neural stem cells and mouse cerebellar precursors and analyzed them both in vitro and in vivo. In vivo analyses revealed that FOXR2 expression alone is sufficient to induce tumors and introducing dominant-negative p53 accelerated that tumor growth. In vitro analyses suggest that FOXR2 interacts with MYCN, leading to stabilization of the protein. Our data would provide a tentative mechanism of FOXR2 oncogenic potential.